Analisis Frasa pada Teks Naratif dalam Buku Bahasa Indonesia Kelas VII SMP Kurikulum Merdeka - Endah Yustiani; Fairuzah Qolbi; Ninda Alifa; Widini Arti; Asep Purwo Yudi Utomo; Ahmad Ripai (Journal of Creative Student Research, 2023)
Syntaxis analysis on narrative text in Indonesian language book class VII middleschool Merdeka curriculum focuses on analysis of phrases. The purpose of performing phrase analysis on this narrative text is to find, describe, and group into the types of phrases contained in narrative texts "Bola-Bola Waktu", "Pantan Terong yang Instagramable" and "Jelajah Wae Rebo" in the Indonesian language class VII SMP curricullum Merdeka. This study used two research methods, descriptive method with qualitative approach and syntactic theoretical method. Data analyzed is collected by the technique of view and note technique. The results of data analysis are presented in the form of tables with the explanation of each phrase found and grouped according to the type of phrase. In this study produces findings of some types of phrases, among others, noun phrases, verb phrase, adjective phrases, numeral phrases, adverb phrases, and preposition phrases. The benefits that can be obtained from this implementation is to provide knowledge and type of phrases and the reader can understand and learn the contents of this analysis and use it for a good context of language as a result of this analysis.